Dearterialization with mucopexy versus haemorrhoidectomy for grade III or IV haemorrhoids: short‐term results of a double‐blind randomized controlled trial. (24th October 2013) - Denoya, P. I.; Fakhoury, M.; Chang, K.; Fakhoury, J.; Bergamaschi, R.
Abstract: Aim: There is scepticism regarding anatomical rationale and Doppler guidance for ligation of haemorrhoidal arteries. The null hypothesis of this randomized controlled trial (RCT) was that there is no difference in pain following dearterialization or haemorrhoidectomy for grade III/IV internal haemorrhoids in a minimum of three quadrants. Method: This was a single‐centre, double‐blind RCT. Patients were allocated to dearterialization or haemorrhoidectomy. Included haemorrhoids were grade III, prolapsing but reducible; and grade IV, chronic non‐incarcerated. The primary end‐point was pain. Patients with external component, acute incarcerated grade IV or recurrent haemorrhoids were not included. The interventions were dearterialization (with Doppler guidance and mucopexy) or haemorrhoidectomy. The main outcome measure was the Brief Pain Inventory (BPI). Results: Twenty dearterialization patients were comparable to 20 haemorrhoidectomy patients for age ( P  =   0.107), body mass index ( P = 0.559), race ( P = 0.437), American Society of Anesthesiology score ( P = 0.569), comorbidities ( P = 0.592), grade ( P = 0.096), quadrants ( P = 0.222), Fecal Incontinence Quality‐of‐Life Score (FIQOL; P = 0.388), coping ( P = 0.532), depression ( P = 0.505), embarrassment ( P  =   0.842), and Short Form Health Survey (SF‐12) physical components ( P = 0.337), SF‐12 mental components ( P = 0.396) and constipation ( P = 0.628) scores. Dearterialization patients had shorter operative time (36 vs 54 min, P = 0.043) with less pain ( P  =   0.011) and urinary retention ( P  =   0.012). Dearterialization patients had first bowel movement earlier (1.3 vs 4.6 days, P = 0.001), less pain ( P = 0.011) and lower pain intensity ( P  =   0.001). Narcotic requirements were reduced in dearterialization patients (25% vs 100%, P  =   0.001), with less medication (4.9 vs 112 pills, P  =   0.001) and shorter regimen (0 vs 7 days, P  =   0.001). BPI did not differ on days 1, 3, 5, 7 and 14 except for less pain in dearterialization patients. At 3 months, symptomatic relief was the same with no differences in BPI, FIQOL or SF‐12. Conclusion: Compared with haemorrhoidectomy, dearterialization led to less pain in grade III/IV haemorrhoids.